BEARing Back: Russian Military Power in the Indo-Asia-Pacific under Vladimir Putin - Muraviev, Alexey (Australian Strategic Policy Institute, 2018)
Current perceptions of Russia as a power factor in the Indo-Asia–Pacific (IndAsPac) geopolitical system are very much influenced by established post-Cold War assumptions that Moscow is no longer able to influence the regional geostrategic landscape because of its reduced military power and limited economic engagement with the region, and thus should be disregarded as a player worth considering and factoring into any strategic calculus.